2022
DOI: 10.3389/fendo.2021.841668
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Network Pharmacology and Experimental Validation to Explore the Pharmacological Mechanisms of Zhuanggu Busui Formula Against Osteoporosis

Abstract: Osteoporosis (OP) is a common skeletal disease, characterized by decreased bone formation and increased bone resorption. As a novel Chinese medicine formula, Zhuanggu Busui formula (ZGBSF) has been proved to be an effective prescription for treating OP in clinic, however, the pharmacological mechanisms underlying the beneficial effects remain obscure. In this study, we explored the pharmacological mechanisms of ZGBSF against OP via network pharmacology analysis coupled with in vivo experimental validation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It is hypothesised that the inhibitory effect of AC on osteoclast function may outweigh its impact on bone production, resulting in protection against bone loss. Prior studies have revealed that OVX mice exhibit an abnormally high expression of osteoclasts-specific markers, such as NFATc1, c-Fos, Mmp9, and Cathepsin K ( 39 , 40 ), Furthermore, the increased expression of genes linked with osteoclasts relies on the activation of NF-κB signaling ( 41 43 ). c-Fos is a critical factor for NFATc1 activation, and NFATc1 functions as the most transcription factor responsible for regulating the expression of osteoclast-specific genes, including Mmp9 and Cathepsin K ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that the inhibitory effect of AC on osteoclast function may outweigh its impact on bone production, resulting in protection against bone loss. Prior studies have revealed that OVX mice exhibit an abnormally high expression of osteoclasts-specific markers, such as NFATc1, c-Fos, Mmp9, and Cathepsin K ( 39 , 40 ), Furthermore, the increased expression of genes linked with osteoclasts relies on the activation of NF-κB signaling ( 41 43 ). c-Fos is a critical factor for NFATc1 activation, and NFATc1 functions as the most transcription factor responsible for regulating the expression of osteoclast-specific genes, including Mmp9 and Cathepsin K ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC‐related targets were retrieved from Online Mendelian Inheritance in Man (OMIM, https://omim.org/), GeneCards (https://www.genecards.org/), and DisGeNET (https://disgenet.org/) (Gao, Mi, et al., 2022; Zhang et al., 2022). Used the keyword “non‐small cell lung cancer” as a search term to remove duplicate target genes.…”
Section: Methodsmentioning
confidence: 99%
“…org/ ), and DisGeNET (https:// disge net. org/ ) (Gao, Mi, et al, 2022;Zhang et al, 2022). Used the keyword "non-small cell lung cancer" as a search term to remove duplicate target genes.…”
Section: Identification Of Nsclc-related Gene Targetsmentioning
confidence: 99%
“…To find the target protein associated with the disease, search the disease database. [ 27 , 28 ] To obtain the gene set of AVNFH, the search results from these databases were combined and deduplicated.…”
Section: Methodsmentioning
confidence: 99%